High Sulfur Loading Cathodes Fabricated Using Peapodlike, Large Pore Volume Mesoporous Carbon for Lithium–Sulfur Battery - Li, Duo; Han, Fei; Wang, Shuai; Cheng, Fei; Sun, Qiang; Li, Wen-Cui (ACS applied materials & interfaces, 2013)
Porous carbon materials with large pore volume are crucial in loading insulated sulfur with the purpose of achieving high performance for lithium–sulfur batteries. In our study, peapodlike mesoporous carbon with interconnected pore channels and large pore volume (4.69 cm3 g–1) was synthesized and used as the matrix to fabricate carbon/sulfur (C/S) composite which served as attractive cathodes for lithium–sulfur batteries. Systematic investigation of the C/S composite reveals that the carbon matrix can hold a high but suitable sulfur loading of 84 wt %, which is beneficial for improving the bulk density in practical application. Such controllable sulfur-filling also effectively allows the volume expansion of active sulfur during Li+ insertion. Moreover, the thin carbon walls (3–4 nm) of carbon matrix not only are able to shorten the pathway of Li+ transfer and conduct electron to overcome the poor kinetics of sulfur cathode, but also are flexible to warrant structure stability. Importantly, the peapodlike carbon shell is beneficial to increase the electrical contact for improving electronic conductivity of active sulfur. Meanwhile, polymer modification with polypyrrole coating layer further restrains polysulfides dissolution and improves the cycle stability of carbon/sulfur composites.